Counter-terrorism, smart power and the United States - Eadie, Pauline (Wiley, 2016)
This article examines smart power, specifically in relation to US counter-terrorism initiatives, focusing on US foreign aid as a soft power instrument. Economic aid and military aid are disbursed under the auspices of USAID and the military is tasked with soft and hard power strategies that have proven problematic to manage as ‘an integrated grand strategy’. Identifying variables that accurately indicate the success or otherwise of smart power as a counter-terror strategy is problematic. Nevertheless a tentative correlation can be drawn between high levels of US aid and low levels of trust in the US in frontline Islamic states. This has led to slippage between hard and soft power and un-smart policy. Consequently a gap has emerged between what the US hopes that the international community will respond to in terms of smart power as a counter-terror initiative and what actually happens. The US has tended to revert to hard power tools in the face of this gap. I argue that foreign aid must not only be soft but ‘sticky’ in order for smart power strategies to succeed.